Influence of age on the association between primary hemifacial spasm and arterial hypertension. Issue 7 (1st July 2003) - Defazio, G; Martino, D; Aniello, M S; Masi, G; Logroscino, G; Manobianca, G; La Stilla, M; Livrea, P
Abstract : Objective: To investigate the association between primary hemifacial spasm and arterial hypertension. Subjects: 114 patients with primary hemifacial spasm and 228 neurological controls, matched for age, sex, and referral centre, were recruited during an 18 month period from consecutive outpatients attending two neurological institutions. Design: The association between exposure variables and case/control status was examined in conditional logistic regression models, adjusting simultaneously for disease duration and education level. Results: Hypertension was more common among the patients with primary hemifacial spasm than among the controls. The association was independent of age, disease duration, years of schooling, and other diseases (adjusted odds ratio (OR) 2.76 (95% confidence interval (CI), 1.43 to 5.33); p = 0.002). Hypertension was associated with hemifacial spasm in both the left sided group (adjusted OR, 2.76 (1.18 to 6.44); p = 0.02) and the right sided group (adjusted OR, 3.02 (1.13 to 8.1); p = 0.03). The association of hypertension with hemifacial spasm was apparently greater in the age group < 60 years (adjusted OR, 4.2 (1.4 to 12); p = 0.008) than in the age group ≥ 60 years (adjusted OR, 2.5 (CI 1.3 to 4.6); p = 0.005), but the difference in the OR estimates between the two age groups was not significant. Among hypertensive patients, mean age at the diagnosis of hypertension was significantly lower than mean age at the onset of hemifacial spasm in the age group ≥ 60 years, but not significantly different in the age group < 60 years. Conclusions: The findings support the hypothesised association of primary hemifacial spasm with hypertension and raise the possibility that a different mechanism underlies the association in different age groups.